Discursive footwork on the hardwood: players' negotiations of the NBA as a contested racial arena. Issue 3 (3rd July 2021) - Manning, Alex; Suh, Stephen Cho; Green, Kyle
Abstract: Using The Players' Tribune, we interpret how NBA players discuss race within a racialized sporting organisation that is celebrated and marketed as cosmopolitan and a model for social engagement. We find that during the Black Lives Matter movement players draw on and move between varied visions of sport, the NBA, and its relationship to race. Players reject post-racial conceptions of sport and society and highlight the realities of structural racism and interpersonal prejudice within the NBA and society. At the same time, players affirm notions of the NBA as removed from social problems and a leader for positive racial dialogue. These discursive shifts and collisions indicate that while individualistic and less critical conceptions of sport and race persistently circulate, they are also vulnerable to more race-conscious, structural, and critical articulations. Thus, we argue player engagement with sport, race, and politics on platforms like TPT help set the stage for the current wave of anti-racist actions and statements from high-profile athletes across global sport post-2020 and is linked to how the NBA politically orients itself as a racialized professional sports organisation.